She called that thing a mido, but should you call it a mido too? Linguistic experience influences infants’ expectations of conventionality - Henderson, Annette M. E.; Scott, Jessica C. (Frontiers in Psychology, 2015)
Words are powerful communicative tools because of conventionality - their meanings are shared among same language users. Although evidence demonstrates that an understanding of conventionality is present early in life, this work has focused on infants being raised in English-speaking monolingual environments. As such, little is known about the role that experience in multilingual environments plays in the development of an understanding of conventionality. We addressed this gap with 13-month-old infants regularly exposed to more than one language. Infants were familiarized to two speakers who either spoke the same (English), or different (French vs. English) languages. Next, infants were habituated to a video in which one of the speakers provided a new word and selected one of two unfamiliar objects. Infants were then shown test events in which the other speaker provided the same label and selected either the same object or a different object. Our results demonstrate that exposure to at least one other language influences infants’ expectations about conventionality. Unlike monolinguals, bilingual infants do not assume that word meanings are shared across speakers who use the same language. Interestingly, when shown speakers who use different languages, bilingual infants looked longer towards the test trials in which the second speaker labeled the object consistently with the first speaker. This finding suggests that exposure to multiple languages enhances infants’ understanding that speakers who use different languages should not use the same word for the same object. This is the first known evidence that experience in multilingual environments influences infants’ expectations surrounding the shared nature of word meanings. An increased sensitivity to the constraints of conventionality represents a fairly sophisticated understanding of language as a conventional system and may shape bilingual infants’ language development in a number of important ways.